ACROSS CULTURE COMMUNICATION STYLE CHOICES IN WESTERN AND BRITISH CULTURE IN THE LEAP YEAR MOVIE. - Nargis Nargis Nargis; Imtihan - Hanim (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
The different cultures, power distance could be the obstacle in intercultural communication. The aim of this research to identify the types of Cross-Cultural Communication Style Choice between British and American in the Leap Year movie. The researchers attempt to reveal kinds of Cross-Cultural Communication Style Choice between Declan as British and Anna as American for three days. This Qualitative research method analyses data of utterances and are classified into four types of Cross-Cultural Communication Style Choice. The result shows that there are 356 utterances of Anna and Declan. for three days. Anna has 204 utterances with 44,3 % direct style and indirect 5,8 %.. Declan uses 155 utterance with 37 % and 12 % indirect style. British tend to use more indirect styles in expressing their intention to save the interlocutor’s face.Meanwhile, American use direct styles to reveal their intentions as they belong to the high culture communication.Key words: across culture communication,direct style, indirectstyle